Photoluminescence of Zinc Complexes: Easily Tunable Optical Properties by Variation of the Bridge Between the Imido Groups of Schiff Base Ligands. Issue 25 (23rd July 2014) - Dumur, Frédéric; Contal, Emmanuel; Wantz, Guillaume; Gigmes, Didier
Abstract: A series of organic–metal chelate complexes of symmetric tetradentate Schiff base ligands derived from salicylaldehyde and 2‐hydroxy‐1‐naphthaldehyde were designed and investigated. The combination of five nonconjugated flexible spacers and five conjugated rigid spacers with four salicylaldehyde derivatives provided a series of forty complexes. The series of blue to red photoluminescent complexes was investigated by UV/Vis absorption and luminescence spectroscopy in solution and in the solid state as well as cyclic voltammetry. The nature of the bridge in the ligand scaffold was determined to be the main parameter that influences the absorption and the emission color of the investigated zinc(II) complexes. Abstract : Forty Schiff base zinc(II) complexes have been designed and studied for their photoluminescence properties. Interestingly, the nature of the diamine spacer in the ligand is the unique factor that influences the optical properties of the complexes.